PEMBINAAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI LINGKUNGAN IV KELURAHAN SIDOMULIO KECAMATAN MEDAN TUNTUNGAN - Rasmulia Sembiring; Robinhot Gultom; Sahat Parulian Remus Silalahi; Siti Normi; Saur Melianna; Tiur Rajagukguk; Winarto; Sondang Nibulan Marbun; Rommel Sitohang; Rio J. Tambunan; Selamat Siregar; Toman Panggabean; Vera Triyanti (Jurnal Pengabdian Pada Masyarakat METHABDI, 2021)
Community Service aims to foster micro, small and medium enterprises (MSMEs) is to provide input on what businesses can be developed in accordance with the conditions in the environment and in accordance with current conditions, namely the Covid 19 pandemic that has hit the city of Medan and the world in general. The community that will be trained are people who live in Environment IV, Sidomulio Village, Medan Tuntungan District, totaling 25 people whose livelihoods are as farmers and as farm laborers. The availability of adequate academics in giving lectures on the Development of Micro, Small and Medium Enterprises (MSMEs) at the Management Study Program, Faculty of Economics, Indonesian Methodist University, the enthusiasm of the participants, the support of the Village Head and the Head of the Environment for the implementation of activities and supporting funds from UMI are supporting the implementation of this PPM activity. The problem is the limited time for coaching. It is hoped that this training will benefit the community. The benefits that participants get from this PPM activity include being able to understand and develop micro, small, and medium enterprises.